The Effect Of Averrhoa Bilimbi Linn With Different Doses On The Fertilization Rate and Hatching Rate Of Asian Redtail Catfish (Hemibagrus nemurus Valenciennes, 1840) Eggs - Mega Novia Putri; Nur Asiah; Sukendi Sukendi (Berkala Perikanan Terubuk, 2022)
The research was carried out in August-September 2021 at the Fish Hatchery and Breeding Laboratory, department of Aquaculture, Faculty of Fisheries and Marine, Riau University. The aim of this research was to determine the effect of A.bilimbi solution with different doses on fertilization and hatching rate of eggs. The method used Completely Randomized Design (CRD) with 4 levels of treatment ; P0 (0 ml/L), P1 (3,5 ml/L), P2 (4,0 ml/L) and P3 (4,5 ml/L). Asian redtail catfish eggs were soaked in a solution of A.bilimbi for 10 minutes in a basin with an egg density of 552 eggs (1 gram) then incubated in an aquarium. Asian redtail catfish larvae were reared for 20 days. Parameters measured in this study were egg adhesion, fertilization rate, incubation time, hatching rate, absolute weight growth, absolute length growth, specific growth rate (LPS), survival rate (SR), and water quality. The results showed that the dose of A.bilimbi solution had a significant effect (P<0.05) on the degree of fertilization and hatching of Asian redtail catfish eggs. A.bilimbi treatment with a dose of 4.0 ml/L resulted adhesion 28.38%, fertilization rate 85.57%, hatching time 23 hours 21 minutes, hatching rate 82.59%, absolute length growth of 2,14 cm, weight growth absolute 0.266 g, specific growth rate 1.31% and survival rate (SR 20) 82.12%. The water quality parameters in the hatchery of Asian redtail catfish eggs are temperature 26.5oC - 27oC, pH 6.7-7.5 and dissolved oxygen (DO) 4.2 mg/L - 4.5 mg/L.